you question doesn't make much sense.
how can (x + 4) be the exponent from the base of 3?
resolve the following exponential equation
3 ^ (x + 4) = 5 ^ (x + 2)
5 answers
(x+4) log 3 = (x+2) log 5
(x+4)/(x+2) = log 5/log 3 = 1.46497
x + 4 = 1.46497 x + 2.92995
0.46497 x = 1.07005
x = 2.3013..
(x+4)/(x+2) = log 5/log 3 = 1.46497
x + 4 = 1.46497 x + 2.92995
0.46497 x = 1.07005
x = 2.3013..
There is nothing wrong with the question. Ignore Hannie's comment.
(x+4)log3 = (x+2)log5
(x+4)(0.47712) = (x+2)(0.69897)
0.47712x + 1.90848 = 0.69897x + 1.39794
0.22185x = 0.51054
x=2.301
Checking you will probably find a small rounding error. If you carry the calculations to a lot of decimal places it will be more exact.
(x+4)(0.47712) = (x+2)(0.69897)
0.47712x + 1.90848 = 0.69897x + 1.39794
0.22185x = 0.51054
x=2.301
Checking you will probably find a small rounding error. If you carry the calculations to a lot of decimal places it will be more exact.
thanks so much! i was sure it had logs involved but wasn't sure. thanks drwls and quidditch!